OPTIMASI SINTESIS BIOSURFAKTAN KARBOHIDRAT ESTER DARI ASAM PALMITAT DAN FRUKTOSA MENGGUNAKAN ENZIM LIPASE TERIMOBILISASI - Hiskia Arapenta Ginting; Zuhrina Masyithah; Tjahjono Herawan; Denny Samuel Silaen (Talenta Publisher (Universitas Sumatera Utara), 2017)
Carbohydrate ester is one of many needed nonionic surfactant groups and has the potential to be an environmental friendly surfactant. The principal problem in the synthesis of carbohydrate ester is to obtain the optimum conversion of palmitic acid from temperature influence, the amount of biocatalyst and reaction time. The optimization of carbohydrate ester synthesis is carried out on three variables that influence the esterification reaction. Therefore, the esterification process is carried out by reacting directly the palmitic acid and fructose using a Novozyme®435 an immobilized lipase enzyme catalyst with a free variable of reaction temperature of 41,5 oC, 45 oC, 50 oC, 55 oC, 58,4 oC, the amount of biocatalyst is 6,63%, 8%, 10%, 12%, 13,36% mass based palmitic acid also reaction time of 7,6 hours; 24 hours; 48 hours; 72 hours; 88,3 hours and reacted with fixed variable in 500 rpm; 3:1 substrate ratio (fructose:palmitic acid) and solvent amount 10 ml. The mixture is then separated from the catalyst by filtration. The product was analyzed with determination of acid number to obtain conversion percent of fructose ester, determination of Hydrophilic Lipophilic Balance, Fourier Transform Infrared (FTIR) an surface tension determination. The optimum conversion rate obtained is 61,80% at 55 oC of reaction temperature, Novozyme®435 enzyme count is 12% and 72 hours of reaction time. From the result of fructose ester surfactant analysis obtained HLB 10,592 value which showed fructose ester surfactant can be used as emulsifier of oil in water.